PENGARUH RETURN ON EQUITY, DEBT TO EQUITY RATIO, CURRENT RATIO, DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR TEKSTIL DAN GARMEN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2019-2023 - Qathul Jamalah, Luha; Badariah, Elis; Abdurrohman, Abdurrohman; Maya Andara, Adissya; Nugrahaeni, Indina Dhesta (LP2M Universitas Bina Bangsa, 2025)
The company value is correlated with the stock price so that if the stock price increases, there is a possibility that the company value will also increase. This study aims to examine the effect of Return on Equity, Debt to Equity Ratio, Current Ratio, and Company Size on Company Value. This study uses a causal associative research method with a quantitative approach. The sampling technique in this study used Purposive Random Sampling so that the companies sampled amounted to 12 Textile and Garment Companies Listed on the Indonesia Stock Exchange. The type of data used in this study is secondary data panel data obtained from annual financial reports published on the Indonesia Stock Exchange for the 2019-2023 period. Research data testing starts from descriptive statistical analysis, classical assumption test, multiple linear regression analysis, hypothesis testing, and determination coefficient test. The results showed that partially ROE has no positive and insignificant effect on Company Value (PBV), DER and CR have a positive and significant effect on Company Value (PBV), Company Size has a negative and significant effect on Company Value (PBV). While simultaneously the ROE, DER, CR, and Company Size variables together have a positive and significant effect on Company Value (PBV).